The Impact of Zakah, Islamic Financing, Sukuk and Inflation on National Economic Growth with Poverty as a Moderation Variable - Musalim Ridlo; Ahmad Mifdlol Muthohar; Khalim Mudrik Masruhan (Falah: Jurnal Ekonomi Syariah, 2021)
The aims of this study is to analyze the influence of zakah, Islamic financing, sukuk and inflation on national economic growth with poverty variable as a moderating variable. This study is quantitative uses secondary data types with the panel data model, namely quartly data from the variable zakah, Islamic financing, sukuk, inflation, poverty, and economic growth in Indonesia period 2014-2018. The  data  collected through annual report and official report and tested using  moderated regression  analysis  (MRA)  models  with  using  Eviews 10 version. The result found that zakah had a significant positive effect on national economic growth, while Islamic financing  had a significant negative effect on national economic growth. On the other hand, sukuk and inflation had a no significant effect on national economic growth. This study combines philanthropic and macroeconomic variables and uses moderation variables that did not exist before, so that it will be something new in quantitative research.